Community leaders’ experiences of hepatitis E in a Namibian informal settlement: A qualitative study - Abraham V. Nghikevali; Talitha Crowley (Journal of Public Health in Africa, 2025)
Background: The hepatitis E virus (HEV) is a major global health concern, with an estimated one-third of the human population infected. It is particularly prevalent in developing countries, especially in informal settlements where inadequate sanitation and limited access to clean water contribute to its spread.